Snacks a partir de productos de mar, pseudocereales y edulcorantes naturales - Gómez Zapata, Guido Martin (2024)
Child malnutrition is one of the problems that most afflicts society, generating around 7,000 child deaths daily worldwide (UNICEF, 2018). The Piura region presents malnutrition rates around 13.1% in children under 5 years old reported during the last years by the Peruvian Ministry of Health. Child malnutrition is summarized in the null or low consumption of nutrients, by ingesting foods with low nutritional intake. Thus, the objective of this study is to review the existing literature on the production of snacks using seafood products, pseudocereals and sweeteners with little processing that will allow a future food supply, taking advantage of the resources available in the region (squid and sugar cane juice). Compiling research articles in the following databases: Taylor and Francis, Science Direct, Google Scholar, Springer, Peruvian university repositories. The results show different experimental studies using mainly pota (Dosidicus gigas); quinoa (Chenopodium quinoa); kiwicha (Amaranthus caudatus); Stevia (Stevia rebaudiana); with acceptable nutritional and sensory qualities.